Bycicles: a case of Indian experience - United Nations Industrial Development Organization (New York, Nations Unies, 1971)
This series of publications, of which the present study on bicycles is the first, is aimed at facilitating the establishment or expansion of the above forms of organization in the developing countries.
.United Nations Publication. No. E.69. II. B.30
osa 22/01/19
Loans
Keywords: Bicycle industry